Proses Peningkatan Kemampuan Teknik Bernyanyi dengan Vokal Chest Register pada Kelompok Mahasiswa Peminatan Vokal - Estervania, Jessica; Langgu, Paskalis R. (Universitas Muhammadiyah Magelang, 2026)
This study aims (1) to identify the process of improving singing technique using the chest register in students specializing in vocal studies, and (2) to describe the effect of improving chest register ability on vocal quality, emotional expression, and song interpretation among vocal specialization students. This study employs a qualitative approach with a field research method. The qualitative approach is used to gain an in-depth understanding of the process of improving singing ability through the chest register vocal technique, including changes in students’ skill development and responses during the learning process. The field research method is applied to improve vocal learning practices through stages of planning, implementation, observation, and reflection on the direct application of the chest register technique in the field. Data were collected through observation, field practice, interviews, and documentation. The data analysis technique used in this study is descriptive qualitative analysis. Data were obtained from pre-tests conducted to determine students’ initial abilities before the training process and post-tests to identify their development and improvement after the training was implemented. The results show that the process of improving singing technique using the chest register was effectively carried out through face-to-face learning, with a focus on initial understanding of the chest register concept, chest resonance, application in the model song Syukur by Husein Mutahar, articulation, breath control, intonation, and expression. The improvement was indicated by a thicker, more powerful, and more stable vocal tone.